2014
DOI: 10.15255/cabeq.2013.1902
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Scenedesmus sp. through Optimized in situ Acidic Transesterification Process

Abstract: Biodiesel production from Scenedesmus sp. was optimized through in situ transesterification via acid catalysis associated with high pressure homogenization pretreatment. Response Surface Methodogy (RSM) was applied to investigate the influence of catalyst amount and biomass to solvent ratio as two major factors for in situ transesterification by central composite method. Optimized reaction conditions were determined as H 2 SO 4 amount of 5.46 % and biomass to methanol ratio of 1:22.07 at 70 ºC for 10 hrs react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Heterogeneous catalysts mainly involve the use of a solid base catalyst, which can easily be separated from the transesterified product, and is always active at the boiling point temperature of methanol during transesterification [39]. In support of this claim, Choi [40] reported that the heterogeneous catalyst is recoverable, less corrosive, produces no soap, and can be reused. Therefore, researchers have tested varieties of solid base for the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous catalysts mainly involve the use of a solid base catalyst, which can easily be separated from the transesterified product, and is always active at the boiling point temperature of methanol during transesterification [39]. In support of this claim, Choi [40] reported that the heterogeneous catalyst is recoverable, less corrosive, produces no soap, and can be reused. Therefore, researchers have tested varieties of solid base for the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, biodiesel production from Scenedesmus sp. through optimized in situ acid in a transesterification process has been carried out by Xie [40]. The study used Minitab RSM version 16 to examine the process analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, this could have some beneficial effects for some very extended applications of residual microalgae such as the extraction of lipids from microalgae cells or anaerobic digestion, which would be useful for the subsequent valorization of the harvested microalgae (e.g. obtention of biogas or biodiesel) (Choy et al, 2014;Ramos-Suárez et al, 2014). If the objective is to recover living microalgae, it is evident that this procedure should be modified.…”
Section: Regeneration and Reusability Of Fe 3 O 4 Npsmentioning
confidence: 99%
“…Meanwhile, catalytic conversion of oil to biofuel could entail the use of homogeneous (NaOH/KOH) or heterogeneous (derived from solid materials) catalysts [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The major shortcomings when homogeneous catalysts are used in production of biofuel are the problems recycling from the products and related problems which can lead to soapy formation, high oil and –OH required, health effects and cost required to purify the products [21] .…”
Section: Introductionmentioning
confidence: 99%